2003
DOI: 10.1046/j.1365-3040.2003.00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of genotypic variation in stress gene expression and photosynthetic parameters in potato

Abstract: Frost injury in potato can involve the interaction of both freezing temperatures and high light. Thus frosts can result in accumulation of activated oxygen species that change the redox potential of cells. Activated oxygen species can either act as signals that induce protection mechanisms or accelerate injury. In comparison with Solanum tuberosum L., Solanum commersonii Dun., is better adapted to low temperature. In this study the freezing tolerance was studied by isolating the cold-regulated genes glutathion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
1
7
0
2
Order By: Relevance
“…The ability of the plants to minimize the oxidative stress depends upon the effectiveness of the antioxidants, which has been reported to vary according to the plant species and their genotypes (Blokhina et al, 2003;Seppanen and Coleman, 2003). From these results it is clear that AGB002 showed superior expression of antioxidant enzymes on exposure to cold stress than ABG025.…”
Section: Antioxidant Enzymesmentioning
confidence: 93%
See 2 more Smart Citations
“…The ability of the plants to minimize the oxidative stress depends upon the effectiveness of the antioxidants, which has been reported to vary according to the plant species and their genotypes (Blokhina et al, 2003;Seppanen and Coleman, 2003). From these results it is clear that AGB002 showed superior expression of antioxidant enzymes on exposure to cold stress than ABG025.…”
Section: Antioxidant Enzymesmentioning
confidence: 93%
“…The ability of the plants to minimize oxidative stress depends upon the effectiveness of enzymatic and non-enzymatic antioxidants (Blokhina et al, 2003;Seppanen and Coleman, 2003). The antioxidant potential is highly variable in different plant species and in different genotypes of the same species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with a potato population derived from a self-pollinated somatic hybrid revealed that antioxidative capacity plays an important role in frost tolerance. Various genes responding to low temperatures or associated with accumulation of active oxygen species at low temperature and intensive light were identified Fagerstedt 2000, Seppänen andColeman 2003). These studies were continued to increase understanding of the genetic and physiological basis of the nonacclimated freezing tolerance in potato.…”
Section: Potato Biotechnologymentioning
confidence: 99%
“…The environmental sensitivity of photosynthesis has allowed it to be used to screening for genetic differences in stress tolerance in several species (Fracheboud et al , Sharma et al , Zhou et al ). In potato, however, there are only few studies and little is known about the photosynthetic capacity of potato under different types of environmental stresses (Seppänen and Coleman , Hassanpana , M'Hamdi et al , Anithakumari et al ). Other studies report only small or even no differences between genotypes of potato for photosynthetic traits (Havaux and Davaud , Balemi and Schenk ).…”
Section: Discussionmentioning
confidence: 99%